THE INTERLACING MAXIMS AS REFLECTED IN THE ENGLISH STUDENTS’ VERBAL COMMUNICATION - Rachmawati Rachmawati; Tubagus Zam Zam Al Arif (JAMBI-ENGLISH LANGUAGE TEACHING, 2020)
The current research serves to portray the interlacing maxims which are reflected in the English Department students’ verbal communication and to depict the politeness which is manifested in the realization of those maxims holistically on the basis of the existing context of speech. The research is designed in the descriptive- qualitative-interpretative by means of the interactive model. This model comprises three research lines, namely: data reduction, data display, and data conclusion/ verification. The data for the present research were gathered repeatedly up to they are exhausted. In terms of data reduction, it is carried out by decreasing the unnecessary utterances or by maintaining the utterances that confirm the graciousness. The utterances that confirm the maxims and graciousness are displayed for having the analysis. The analysis are verified several times up to the researchers come at the equal conclusion. Accordingly, the research engages a group (class) of students as the research participants and it reveals the sequence of maxims, i.e., (1) the Tact maxim, (2) the Generosity maxim, (3) the Approbation maxim (4) the Modesty maxim, and (5) the Agreement maxim conveyed in the diverse contexts by the English Department students at Faculty of Teacher Training and Education, Jambi University.